2023
DOI: 10.1186/s41239-023-00398-2
|View full text |Cite
|
Sign up to set email alerts
|

Digital literacies, social media, and undergraduate learning: what do students think they need to know?

Abstract: This research addresses an identified need to further understand digital literacies (DL) and whether undergraduate students view DL as being important in their lives and in their learning. Using a cross-sectional survey sent to a stratified random sample of 2500 undergraduates representative of the overall student population at a medium-sized Canadian undergraduate university (survey response rate of 19.8%, N = 496), we explored the relationships between social media and digital literacies, particularly in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 35 publications
(43 reference statements)
0
0
0
Order By: Relevance
“…Existing literature on internet use and engagement underscores a focus on gender disparities and academic levels. While Smith and Storrs (2023) emphasize a bias towards undergraduate participants, Smith and Caruso (2010) delve into gender-specific engagement patterns, revealing variations in participation, communication styles, and preferences. Sun et al (2020) highlight gender differences in internet use patterns, prompting further exploration into their impact on online learning environments.…”
Section: University Students' Engagement In Online Learning Environme...mentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature on internet use and engagement underscores a focus on gender disparities and academic levels. While Smith and Storrs (2023) emphasize a bias towards undergraduate participants, Smith and Caruso (2010) delve into gender-specific engagement patterns, revealing variations in participation, communication styles, and preferences. Sun et al (2020) highlight gender differences in internet use patterns, prompting further exploration into their impact on online learning environments.…”
Section: University Students' Engagement In Online Learning Environme...mentioning
confidence: 99%
“…The distribution of participants across different study levels is consistent with the existing literature. This literature often reports a higher prevalence of undergraduate participants Jiang et al Int J Educ Technol High Educ (2024) 21:41 in studies involving large populations (Smith & Storrs, 2023). A significant majority of Chinese university students allocate 1-2 h (17.8%), 3-4 h (33.9%), and 5-6 h (20.9%) to internet usage daily.…”
Section: Gender Distribution and Level Of Engagement And Internet Add...mentioning
confidence: 99%
“…Furthermore, E. Smith and H. Storrs (Smith & Storrs, 2023) examine the essential topic of undergraduate students' digital literacy (DL). Their study, which included 2500 undergraduates, revealed a large gap in students' digital literacy instruction, particularly in the context of social media.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research finding showed that the aplication of hybrid learning benefited the lecturers and also the students in some aspects; one of them is the students' improvement in grammar achievement and their digital literacy (Vonti & Rahmah, 2019). Students report using social media in their higher education learning, showing that students value social media for collaboration, discussion, information fnding and sharing, and practice activities related to their learning (Smith & Storrs, 2023).…”
Section: Security (E-safety)mentioning
confidence: 99%